All God's mistakes - Bosk, Charles L. (Univ. of Chicago Press, 1992)
Genetic testing has become so precise that doctors can detect even the most subtle defects in fetuses at almost any time in a pregnancy. But what happens when a woman is told she is carrying a damaged fetus? What advice should be given to those at risk of bearing genetically defective children? How are birth defects explained to parents? In All God's Mistakes Charles Bosk takes readers inside the hospitals and laboratories where these dilemmas are confronted daily. From his fieldwork with a genetic counseling team in an elite urban medical center, Bosk shapes a remarkable account of the clinical applications of human genetics in medicine. His finely drawn observations form the basis for an often provocative portrait of the scientific, ethical, and professional conflicts that surround use of the new technologies of conception and prenatal diagnosis in the larger society. In one fascinating case after another, Bosk reveals the process by which physicians and other health professionals come to make decisions about pregnancies. A compelling depiction of both extraordinary drama and ordinary routine, this is a pioneering case study of authority and control in a pediatric hospital, showing how genetic counselors work with colleagues and with patients, and how they deal with their powerlessness to control life-and-death decisions that they must address. The first book of its kind, All God's Mistakes will be of considerable value as a source for informed decision making to the increasing number of people affected by the professional and personal consequences of the new medical technology.